Predictive parameters of cardiovascular risk in younger school-age children - Sulinová, Zlatana; Dorko, Erik; Rimárová, Kvetoslava; Diabelková, Jana; Tejová, Martina; Houžvičková, Andrea (Central European journal of public health, 2024)
OBJECTIVES: Overweight and obesity are important concerns for global health. They are characterized by excessive fat accumulation that can harm health. Childhood obesity has reached alarming levels around the world due to urbanization and changes in lifestyle. This trend highlights an urgent need for effective public health strategies to promote healthier lifestyles, prevent chronic diseases, and support the wellbeing of future generations. This study aimed to monitor the impact of the risk factors on blood pressure and lipid profile parameters. METHODS: Data were collected from 267 school-age children from Slovakia. The study assessed blood pressure using the sphygmomanometer technique, where systolic (SBP) and diastolic (DBP) blood pressure were measured in a seated position and repeated three times. The pulse rate was evaluated using Ruffier's physical fitness test. Anthropometric measurements included body weight, height, waist circumference, hip, and chest circumference, body mass index (BMI), and fat skinfolds measurement. The children's parents completed a comprehensive questionnaire. The data were statistically evaluated using IBM-SPSS version 19. RESULTS: Our analysis showed a statistically significant difference in SBP between obese and non-obese children (p < 0.001), but no significant differences for DBP and total cholesterol. Similar results were found between normal-weight and overweight children for SBP (p < 0.001), with overweight children showing higher SBP. No significant differences were noted for DBP or total cholesterol. Among children with "bad fitness", 57.9% had elevated SBP, compared to 37.86% with "good fitness" (p < 0.01). Additionally, 41.67% of children with bad fitness had elevated DBP, versus 23.05% in good fitness (p < 0.001). Significant differences in total cholesterol were also observed in these two groups (p < 0.05). CONCLUSIONS: The results of this study confirm the importance of monitoring risk factors that significantly influence cardiovascular parameters.
Keywords: risk factors; kardiovaskulární nemoci; Humans; systolic blood pressure; index tělesné hmotnosti; Body Mass Index; cholesterol; school-age children; dítě; rizikové faktory kardiovaskulárních chorob; Child; Pediatric Obesity; Female; rizikové faktory; lidé; Slovakia; Slovenská republika; ženské pohlaví; Cardiovascular Diseases; krevní tlak; obezita dětí a dospívajících; Male; Heart Disease Risk Factors; diastolic blood pressure; mužské pohlaví; Blood Pressure; obesity; Risk Factors